Framing texts and images of Latin America’s official, online climate change news’ articles - Fátima Viteri Mancero (Razón y Palabra, 2017)
The purpose of this study is to reconstruct educational frames in texts and images of official, online climate change news’ articles in Latin America, which have remained largely unexplored. Qualitative content analysis of regional news in 2014 was applied to reconstruct educational frames found in texts (14) and images (35). Findings showed mainly educational frames aimed at cognitive processes such as knowledge acquisition and comprehension. Articles presented in a hypertextual environment may have implications for readers’ learning. Further study is required for comparative purposes.